Modifikasi Algoritma Kriptografi RSA Multiprima Menggunakan Chinese Remainder Theorem dan Garner’s Algorithm - Fatimah Putri Johari; Dewi Murni; Hendra Syarifuddin (UNIVERSITAS NEGERI PADANG, 2019)
Abstract–Cryptographic algorithms multiprime RSA (Rivest-Shamir-Adleman) is one of the public key cryptographic algorithms that are widely used, because the algorithm is easily applied and security is also guaranteed. But on the other hand this algorithm has drawbacks, namely the process of decryption a takes a relatively long time because using modular exponentiation. To address this, it will do modifications to the process of decrypting RSA Cryptographic algorithms multiprime by finding a method that can cut the number of modular exponentiation operation is great modular exponentiation operation into several smaller ones. This modification is only focused on the process of decryption is done by leveraging the next reminder: chinese theorem can be solved using Garner's algorithm. This modification of the results obtained a new private key used for decryption process Keywords –Cryptography, Multiprime RSA, Chinese Remainder Theorem(CRT), Garner’s Algorithm